2005
DOI: 10.1238/physica.topical.115a00749
|View full text |Cite
|
Sign up to set email alerts
|

XAFS and XRD Studies of PdOCeO2 Catalysts on Al2O3

Abstract: Alumina-supported PdO is largely accepted as an effective catalyst for the methane combustion reaction. In this study, we investigated the influence of the addition of CeO 2 to the PdO catalysts supported on -Al 2 O 3 on their microstructures by XAFS spectroscopy and X-ray diffraction technique (XRD).We obtained the radial structure functions (RSF) from Fourier transform of Pd K-edge EXAFS spectra of both fresh and as-tested catalysts for the PdO and PdO-CeO 2 system on alumina, respectively. A single peak, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…A role of CeO2 is to suppress the crystal growth of PdO in the catalyst upon elevating the temperature, and it is tentatively concluded that the high catalytic activity at R = 1 comes from the small crystallite size of PdO as well as the largest surface area, as has been reported before. 5 Figure 2 illustrates the XP spectra of Pd in two catalysts of R = 0 (a) and R = 1 (b) before and after reducing in a methane atmosphere at 300˚C; two peaks due to the emission of photoelectron from the inner-core orbitals, 3d3/2 and 3d5/2, of the Pd atom, were observed. A significant shift of these two peaks by as much as 1.9 -2.9 eV to the lower binding energy side was observed in common after these catalysts were treated in a reducing atmosphere of methane at 300˚C, although an unshifted peak is still observed as a shoulder in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A role of CeO2 is to suppress the crystal growth of PdO in the catalyst upon elevating the temperature, and it is tentatively concluded that the high catalytic activity at R = 1 comes from the small crystallite size of PdO as well as the largest surface area, as has been reported before. 5 Figure 2 illustrates the XP spectra of Pd in two catalysts of R = 0 (a) and R = 1 (b) before and after reducing in a methane atmosphere at 300˚C; two peaks due to the emission of photoelectron from the inner-core orbitals, 3d3/2 and 3d5/2, of the Pd atom, were observed. A significant shift of these two peaks by as much as 1.9 -2.9 eV to the lower binding energy side was observed in common after these catalysts were treated in a reducing atmosphere of methane at 300˚C, although an unshifted peak is still observed as a shoulder in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4,5 In a small volume of an aqueous solution of Ce(NO3)3·6H2O, a weighed portion of Al(OH)3 (gibbsite) was suspended and admixed by vigorous stirring for 30 min. An aqueous solution of Pd((NO3)2 was added to the mixture in various atomic ratios of R = Ce/Pd.…”
Section: Chemicalsmentioning
confidence: 99%
See 3 more Smart Citations